Asfah Bioenergy Sdn Bhd. / Nur A’in Rosli - Rosli, Nur A’in (Universiti Teknologi MARA, Perlis, Faculty of Business and Management, 2021)
Asfah BioEnergy is the place where I do industrial training for this semester.Asfah was small medium enterprise (SME) established in May 1996. The product that Asfah produce are the liquid biofuel and solid biofuel. My internship at Asfah Bioenergy Sdn Bhd lasted six months, starting on 1 March 2021 and ending on 13 August 2021. During my internship I was assigned in accounting department under Encik Faiz Ahmad Shah. I also gained a lot of experience and learned a lot of new skills during my internship. In this report also consist of my report research during my internship. The title that I have chosen for this research is Determinants of the Capital Structure: Evidence from Malaysia Food and Beverage Sector. Using a data collection of Malaysian companies, the objective of this research is to analyze the most significant factors that determine capital structure. This is to find the company uses a unique combination of finance and equity to support its overall business and development. This paper carries out a panel data analysis from 10 listed companies in Malaysia under industry food and beverage stock market. The data collected covers the years 2010 through 2019. From data acquired from Refinitiv Eikon, the author uses data analytic techniques to analyze and estimate the most significant determinants of capital structure of listed firms in Malaysia. The study was carried out to see if the selected factor had a significant relationship with capital structure. In this study it consists of four variable which is one for dependent variable and another three are for independent variable. The independent which is leverage, liquidity and effective rate variable shown that have a positive, negative and no significant relationship with the dependent variable. Finally, this is the first study to use the most recent data to investigate the most significant determinants of capital structure in Malaysia.